Creed's honor eaudiobook Montana creeds series, book 6. - Miller, Linda Lael (Creed Cowboy, 2011)
Linda Lael Miller's New York Times best-selling contemporary Western romances have found a place in the hearts of listeners worldwide. Creed's Honor stars Connor Creed, a rancher reluctantly carrying on his uncle's legacy in Lonesome Bend, Colorado. For years he's sacrificed his own dreams to fulfill the promise he made to his uncle. But everything changes when his wild, estranged twin brother re-enters his life-and then there's the beautiful Tricia McCall, who stirs feelings of passion deep within Connor's soul.